Freeze-dried live attenuated smallpox vaccine prepared in cell culture "LC16-KAKETSUKEN": Post-marketing surveillance study on safety and efficacy compliant with Good Clinical Practice. Issue 45 (9th November 2015) - Nishiyama, Yasumasa; Fujii, Tatsuya; Kanatani, Yasuhiro; Shinmura, Yasuhiko; Yokote, Hiroyuki; Hashizume, So
Abstract: Background: In Japan, production of smallpox vaccine LC16m8 (named LC16-KAKETSUKEN) was restarted and was determined to be maintained as a national stockpile in March 2002. Objective: To conduct a post-marketing surveillance study of the vaccination of freeze-dried live attenuated smallpox vaccine prepared in cell culture LC16-KAKETSUKEN using attenuated vaccinia strain LC16m8. The study complied with Good Clinical Practice, focusing on a comparison between primary vaccinees and re-vaccinees. Method: 268 personnel (261 males and 7 females) of the Japan Ground Self-Defense Force were inoculated with LC16-KAKETSUKEN and thereafter adverse events and efficacy were evaluated. Results: Among 268 vaccinee participants, the following vaccinees showed adverse events, none serious: 53 of 196 primary vaccinees (without previous smallpox vaccination), 4 of 71 re-vaccinees (with previous smallpox vaccination) and 1 vaccinee with unknown previous vaccination history. A breakdown of adverse events observed in this study (total 268 vaccinees) showed the following minor or mild adverse events: 52 (19.4%) swelling of axillary lymph node, 4 (1.5%) fever, 2 (0.7%) fatigue, 1 (0.4%) of rash, 14 (5.2%) erythema at the inoculation site, 1 (0.4%) swelling at the inoculation site and 1 (0.4%) autoinoculation. The incidence of adverse events for primary vaccinees (53/196; 27.0%) was significantly higher than for re-vaccinees (4/71; 5.6%). However, the proportion of vaccine take was significantly higher for primary vaccinees (185/196; 94.4%) than for re-vaccinees (58/71; 81.7%). Although the proportion of vaccine take of re-vaccinees was significantly lower than for primary vaccinees due to preexisting immunity by previous vaccination, no significant difference was found in neutralizing antibody titers between primary vaccinees and re-vaccinees at 1, 4 and 7 months after LC16-KAKETSUKEN vaccination. Conclusion: The present post-marketing surveillance study compliant with Good Clinical Practice demonstrated the efficacy and safety of the smallpox vaccine LC16-KAKETSUKEN in an adult population. LC16-KAKETSUKEN is the sole currently available licensed smallpox vaccine for both adult and pediatric populations.